Graphene quantum dots-decorated ZnS nanobelts with highly efficient photocatalytic performances. Issue 29 (2nd March 2016) - Ham, Sooho; Kim, Yeonho; Park, Myung Jin; Hong, Byung Hee; Jang, Du-Jeon
Abstract : Graphene quantum dots-embedded ZnS nanobelts showed 14-times higher photocatalytic activity than commercial ZnS. Abstract : Hybrid nanostructures combining inorganic materials and graphene have shown great potential for the environmentally friendly treatment of effluents. Herein, graphene quantum dots (GQDs)-decorated ZnS nanobelts have been synthesized via a facile hydrothermal method. The electrostatic attraction of two materials and the thermal reduction of graphene are the main driving forces to fabricate well-defined composite nanostructures. GQDs in GQD/ZnS nanocomposites have been found to exist discretely and uniformly on the surfaces of ZnS nanobelts. The photocatalytic activity of GQD/ZnS nanocomposites has been found to be highest at a GQD/ZnS mass ratio of 8 × 10 −4 . The photocatalytic rate constant (0.0046 min −1 ) of GQD/ZnS nanocomposites having the optimized GQD content in the photodegradation reaction of rhodamine B has been found to be 14 times higher than that of commercially available ZnS powder. Decorated GQDs introduce an additional visible-light response and serve as electron collectors and transporters to block electron–hole recombination efficiently, enhancing the photocatalytic performances of ZnS nanobelts immensely.